Liberty and union : the Civil War era and American constitutionalism - Huebner, Timothy S., 1966- (University Press of Kansas, 2016)
"A unique and ambitious study of "the long Civil War Era"--Encompassing the antebellum debates over slavery and sovereignty, the deadly Civil War they spawned, and the transformative postwar outcomes. Integrating political, military, and social history, it focuses on that era's evolving and conflicting views of the Founders' ideals and captures the chameleon-like character of a constitution that inspired contradictory interpretations due to its ambiguous position regarding slavery and the balance of power between federal and state governments"--